2008
DOI: 10.1007/s10802-007-9205-5
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Parenting Processes and Adolescent Substance Use: Reciprocal Effects

Abstract: Drawing on transactional theories of child development, we assessed bidirectional links between trajectories of adolescent substance use and parenting processes from early through mid adolescence. Hierarchical generalized models estimated trajectories for 3,317 adolescents from the National Longitudinal Survey of Youth 1997, exploring both between- and within-individual effects. Between individuals, adolescents reporting more regular family activities and greater father and mother knowledge of friends and teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 30 publications
(38 reference statements)
11
83
0
Order By: Relevance
“…However, because "hard-to-manage" children are known to elicit more negative parenting than their normally developing sibling, it seems logical that they will, on average, be the disfavored sibling. Also, associations between mother and father parental measures corroborate previous findings that parents often have similar parenting strategies within families (Coley et al, 2008). However, associations between one parent's ALP and the other parent's PDT were unexpected and may indicate some compensatory process.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, because "hard-to-manage" children are known to elicit more negative parenting than their normally developing sibling, it seems logical that they will, on average, be the disfavored sibling. Also, associations between mother and father parental measures corroborate previous findings that parents often have similar parenting strategies within families (Coley et al, 2008). However, associations between one parent's ALP and the other parent's PDT were unexpected and may indicate some compensatory process.…”
Section: Discussionsupporting
confidence: 83%
“…Very little existing research has explicitly delineated the processes through which fathers influence their children's behavior (e.g., Cabrera, Shannon, & Tamis-LeMonda, 2007;Coley & Medeiros, 2007), while increasing evidence suggests the importance of a differentiated approach from the mother and the father in promoting child adjustment (Lewis & Lamb, 2003). Although parents often have similar parenting strategies within families, due to both assortative mating and mutual influence and decision-making (Coley, Votruba-Drzal, & Schindler, 2008), research has shown that mothers tend to engage in more frequent interactions with their children and are more responsive than fathers; fathers tend to be more demanding and have more distant relationships with their children (Lewis & Lamb, 2003). Previous studies have found that the correlation between parenting and child EPB tends to be higher for mothers than for fathers (see Rothbaum & Weisz, 1994 for a meta-analytic review), and also that maternal parenting is more strongly predictive of children's EPB than paternal parenting (Aunola & Nurmi, 2005;Gadeyne et al, 2004;Meunier et al, in press).…”
Section: Parental Behavior and Epb Trajectoriesmentioning
confidence: 99%
“…For these reasons, the intercept was no longer under consideration in the analyses. have a consistent effect over time on the construct of interest (Coley, Votruba-Drzal, & Schindler, 2008).…”
Section: Analysis Strategymentioning
confidence: 79%
“…Corroborating findings from research with school age children (Coley et al 2008), it found evidence for father involvement effects. Father involvement at 9 months was negatively associated with internalizing symptoms at 3 years, even after adjusting for father involvement at age 3 and for a wide range of family, area and child influences on children's problem behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…This research usually follows the standard family environment model (Burt et al 2008, for a recent review), which assumes that the type and the quality of the parent-child interaction affect child outcomes, even after taking into account the role of children's characteristics and behaviours in influencing family processes (Coley, Votruba-Drzal and Schindler 2008;Jaffee et al 2004). Most of this research is based on USA samples, and explores associations between father involvement and school age children's outcomes.…”
Section: Introductionmentioning
confidence: 99%